Challenges of banking: modern Russian specificity - Strelnikov, Vladimir V. (Opción, 2020)
The aim of the study is to investigate the challenges of banking as certain Russian specifics, and in the aggregate, requiring system integration and balance in the conditions of active digitalization via the systematic approach and general scientific methods. As a result, new financial relationships, emerging in the context of the widespread development of digital technologies are under the increasing influence of previous state restrictions. This Russian specificity has a significant potential of turning into destructive system factor for banking. In conclusion, the formation of modern ecosystems and technological platforms in Russian formats is mainly carried out by large banks.